The data is falling! - Chandler, Martin (Bulletin - Association of Canadian Map Libraries and Archives (ACMLA), 2025)
This GIS Trends column offers another angle on data preservation (see my "Here Today, Here Tomorrow…" piece from the Summer 2024 issue, linked in the references section below). While last time we discussed the loss of research outputs and the data hosted therein with the retirement of Esri's "Classic Story Maps", today we discuss the loss of more "stable" data sources, namely government sources. As we've seen, even something as simple as the name of a place (see Treisman, 2025 on the Gulf of Mexico) can be changed, though even that can lead to a question of changed for who (see Thiessen, 2025 on Denali).